2021
DOI: 10.1038/s41598-021-02524-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the permeability of crushed coal medium based on the Ergun equation

Abstract: Accurate determination of the permeability of crushed coal medium is the basis for the study of their permeability characteristics. To investigate the permeability characteristics of this special porous medium composed of crushed coal particles, the permeability parameters of crushed coal specimens of different initial porosities were measured by designing a lateral-limit compression seepage test system. Parameters were determined separately for specimens of different initial porosities. (1) the Reynolds numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In cohesive soils, the deformation process mostly includes the friction and bonding strengths [ 25 ]. As a frictional material, the strength of broken coal and rock masses does not include the bonding strength, but due to the unique particle shape, significant occlusion can occur between the particles [ 26 , 27 ]. Therefore, the friction force overcome during deformation of the broken coal and rock masses can be divided into occlusal and sliding friction forces.…”
Section: Discussionmentioning
confidence: 99%
“…In cohesive soils, the deformation process mostly includes the friction and bonding strengths [ 25 ]. As a frictional material, the strength of broken coal and rock masses does not include the bonding strength, but due to the unique particle shape, significant occlusion can occur between the particles [ 26 , 27 ]. Therefore, the friction force overcome during deformation of the broken coal and rock masses can be divided into occlusal and sliding friction forces.…”
Section: Discussionmentioning
confidence: 99%
“…The first member is a linear function of filtration velocity V and refers to laminar flow, and the second member is a quadratic function of filtration velocity V 2 that refers to turbulent flow. The limits of each flow type are determined by the Reynolds number described by Equation ( 2) [36,37]:…”
Section: Laboratory Model Testing Methodologymentioning
confidence: 99%
“…On this basis, it was obtained that the relationship between permeability, non-Darcy coefficient, and porosity of crushed sample can be fitted using an exponential function . Gas permeability experiments with different stress carried out on crushed coal and rock were used to construct a stress-permeability fitting model by varying the stress conditions and the number of cycles of loading and unloading. , Under constant total stress, permeability to sorption gas increases with a decrease of pressure due to crushed coal and rock swelling , and decreases with increasing pressure due to matrix shrinkage. , Pang et al and Zhang et al , studied the permeability evolution of crushed coal with different porosities and found that porosity is the main factor determining the permeability of crushed coal samples.…”
Section: Introductionmentioning
confidence: 99%
“… 36 , 37 Under constant total stress, permeability to sorption gas increases with a decrease of pressure due to crushed coal and rock swelling 38 , 39 and decreases with increasing pressure due to matrix shrinkage. 40 , 41 Pang et al and Zhang et al 42 , 43 studied the permeability evolution of crushed coal with different porosities and found that porosity is the main factor determining the permeability of crushed coal samples.…”
Section: Introductionmentioning
confidence: 99%